Implementasi Pembelajaran Ilmu Hadist di MAN 1 Boyolali saat Pandemi - Abid Nurhuda; Nur Aini Setyaningtyas (Penerbit Goodwood, 2022)
Purpose: The purpose of this PLP 2 activity is one of the educational internship training activities carried out by the Faculty of Tarbiyah Sciences (FIT) IAIN Surakarta. The aim is to produce competitive, high-quality, Islamic, and professional educators. Method: The method used is descriptive qualitative, namely by interviewing the waka of the curriculum, teachers of Hadith Sciences and religious students of classes X, XI, and XII. Followed by participatory observation and documentation. Result: The result was the Implementation of Hadith Science Learning in Man 1 Boyolali During the Pandemic was dominated by WhatsApp and voice notes as the main learning media while zoom, gmeet, google classroom, youtube links, blog links and google forms were only used occasionally. The obstacles encountered include the lack of student activity, limited quota, signal interference, students do not have cellphones and students do not collect assignments. Contribution: Efforts to overcome this are by an appreciation for active students, purchasing cheap unlimited quota packages, finding places with full signals, coordination, and deep communication between the school, students, parents, and teachers.